2016
DOI: 10.1007/s11250-016-1210-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and molecular characterization of porcine Picobirnavirus in piglets of North East Region of India

Abstract: Picobirnaviruses (PBVs) have been recognized as one of the important causal viral agents of gastroenteritis in several animal species especially in young immunocompromised hosts. In this study, we report the prevalence and molecular epidemiology of porcine PBVs from North Eastern Hilly region of India. A total of 457 fecal samples from piglets were collected from local (n = 130) and cross (n = 327) breed piglets in different seasons for 2 years. All the samples were subjected to RNA-PAGE and RT-PCR analysis fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Maternal immunity might also play an important role in resisting the infection in piglets, particularly in indigenous pigs. In the same region in a study of diarrheagenic pathogens, reported a higher prevalence rate of Picobirnavirus and STEC in crossbreed than indigenous piglets population [24,46]. In our study, samples collected during different seasons showed that coinfection of enteric pathogens was found to be most common during the summer (June-August).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Maternal immunity might also play an important role in resisting the infection in piglets, particularly in indigenous pigs. In the same region in a study of diarrheagenic pathogens, reported a higher prevalence rate of Picobirnavirus and STEC in crossbreed than indigenous piglets population [24,46]. In our study, samples collected during different seasons showed that coinfection of enteric pathogens was found to be most common during the summer (June-August).…”
Section: Discussionsupporting
confidence: 56%
“…Detection of Rotavirus Groups A and C was performed by targeting VP7 gene [22] and VP6 gene [23], respectively. For the detection of Picobirnavirus genogroup I (GGI) [24] and GGII [25], specific primers were used. Details of oligonucleotides and PCR conditions used in the present study are given in Table-1 [22][23][24][25][26][27][28][29].…”
Section: Detection Of Rotavirus and Picobirnavirusmentioning
confidence: 99%
See 1 more Smart Citation
“…The phylogenetic analysis revealed genetic similarity to different porcine and human GG-I PBVs from different geographical regions. In 2016, Porcine PBV infection was reported from North Eastern Region of India with strains having varied diversity and were not found to be closely associated with any other Indian isolates of PBVs so far [ 21 ]. The study also claims that PBV infections are higher in acute summer and winter seasons compared to spring and autumn seasons with high prevalence recorded in cross breed pigs in contrast to local breeds.…”
Section: Introductionmentioning
confidence: 99%
“…As reported by Ganesh et al[4] and Fregolente et al[2], PBV prevalence in different mammalian hosts ranges from 12.5 to 14.3%. Particularly in pigs, a recent study conducted by Kylla et al[9] found 11.5% of PBV prevalence as the most significant rate in diarrheal animals.Because PBV can infect humans, employees from farm A were sampled to investigate the presence of the virus in their feces. Fifteen feces samples were collected and analyzed by RT-PCR.…”
mentioning
confidence: 96%